USING TED TALKS IN TEACHING ENGLISH FOR SPECIFIC PURPOSES AT UNIVERSITY LEVEL - Vilkhovchenko Nadiia (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология)
This study considers TED talks as an effective authentic resource for mastering English. The purpose of the article is to outline a methodology for using TED talks in teaching English for specific purposes (ESP) at the university level. To achieve this goal, we set the following objectives: to introduce and describe the steps of utilizing TED talks, as well as provide examples to each step. We applied a number of methods which helped to fulfil the task of the paper. They include establishing the cognitive and educational value of ESP and its place in the system of university education; defining the tasks and its content of the discipline; developing methodical means and organizational forms of training according to these tasks and content. TED talks are informative presentations delivered by experts in their fields. They provide a great opportunity for language teachers to incorporate authentic listening and speaking tasks in their teaching methods. A welldesigned lesson plan that utilizes TED talks as a teaching tool can benefit ESP students in various ways. The methodology of incorporating TED talks in the teaching process should involve a series of steps that aim to maximize effective learning outcomes. These steps include selecting the theme of the talk, searching the TED talk, delivering the speech, designing pre-listening and post-listening activities. The article presents examples of exercises that can be done at each step with reference to specific TED talks from the site https:// ed.ted.com. The first step ensures that the chosen TED talks are suitable and engaging. Teachers can provide students with choices and allow them to vote. The aim of the second step is to support students’ understanding of the TED talk. The third step develops listening comprehension skills. The fourth step engages and promotes students’ active listening skills. The fifth step helps to develop skills of discourse analysis. The video content that the teacher chooses for the lesson should correspond to the professional interests of students. In such a way this video will be able to increase the motivation to study not only a foreign language but also specialized disciplines. The work with TED talks, however, differs from ordinary academic lectures and presentations. Thus, it requires special training of both the teacher and students. Firstly, students` level of English is an important factor defining the choice of a lecture. The teacher considers the level of listening skills, knowledge of the topic, and terminology. Secondly, it is important to take into account the duration of the presentation. If students are not familiar with the topic, they can have some difficulties with comprehension. Therefore, they will need to listen to the lecture twice. So, the preferable length of the video should be about 5-6 minutes. Incorporating TED talks as a teaching tool in English for Specific Purposes can be a highly effective way of promoting active learning in the classroom. TED talks are a source of authentic and relevant topics for students to engage in while providing a more enjoyable and efficient way of learning. The methodology of using videos from the resource has clear benefits. They include improving comprehension skills, vocabulary acquisition, note-taking, and speaking skills. By following the steps mentioned in this paper, lecturers can deliver enriching, pedagogical sessions that will provide students with a foundation to become successful professionals in their respective fields.